Effect of chloride ion on corrosion resistance of Ni-advanced weathering steel in simulated tropical marine atmosphere. (10th January 2021) - Fan, Yueming; Liu, Wei; Sun, Zongteng; Chowwanonthapunya, Thee; Zhao, Yonggang; Dong, Baojun; Zhang, Tianyi; Banthukul, Wongpat
Graphical abstract: Highlights: The effect mechanism of Cl − on corrosion resistance was investigated. The effect of Cl − on corrosion resistance was related to the Cl − concentration. The corrosion resistance reduced with the inhibition of Cl − on NiFe2 O4 enhanced. The transformation from γ-FeOOH to α-FeOOH was limited in high-Cl − environment. Abstract: The effect of chloride ion on corrosion resistance of Ni-advanced weathering steel in simulated tropical marine atmosphere was investigated by surface analysis and electrochemical methods. The results showed that the effect of chloride ion on corrosion resistance of steel was primarily related to chloride ion concentration. As the chloride ion concentration increased, the inhibition of chloride ion on the formation of NiFe2 O4 was gradually enhanced and the corrosion resistance of steel was reduced. Meanwhile, the main composition phase of inner product film changed from α-FeOOH to γ-FeOOH, whereas that of outer film changed from γ-FeOOH to β-FeOOH. Moreover, Ni was mainly concentrated in the inner film instead of being distributed in the whole product film.